Assessing the Economic and Business Implications of Goods and Services Tax (GST) in India: A Comprehensive Analysis (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The introduction of the Goods and Services Tax (GST) in India represented a major transformation in the country’s indirect taxation system, consolidating various taxes into a unified framework. Enforced from July 1, 2017, GST aimed to simplify tax compliance, eliminate cascading effects and establish a transparent taxation mechanism. This paper provides a detailed assessment of GST’s impact on the Indian economy, analyzing its influence on revenue generation, economic growth, industrial performance and consumer welfare. The study delves into the multi-stage, value-added and destination-based characteristics of GST, emphasizing its three components—Central GST (CGST), State GST (SGST) and Integrated GST (IGST)—which govern taxation across intra- and inter-state transactions. Furthermore, an evaluation of GST revenue trends from 2017 to 2022 reveals a consistent rise in collections, despite initial hurdles and a downturn during the COVID-19 pandemic. The findings highlight GST’s role in curbing tax evasion, facilitating seamless interstate trade, enhancing compliance and improving India’s business climate. However, challenges persist, including sectoral tax burdens, compliance costs for small enterprises and the necessity for continuous tax rate adjustments and exemptions. Additionally, the paper discusses GST’s effects on consumers, noting its dual impact of making essential goods more affordable while increasing taxation on certain services.